Patient education interventions for health behaviour change in adults diagnosed with coronary heart disease: A protocol for a systematic review and meta‐analysis. (18th November 2020) - Shi, Wendan; Ghisi, Gabriela L. M.; Hyun, Karice; Zhang, Ling; Gallagher, Robyn
Abstract: Aim: To assess the efficacy of structured patient education on disease‐related knowledge and health behaviour change outcomes in adults with coronary heart disease. Design: Systematic review and meta‐analyses including meta‐regression on education duration. Methods: Seven databases (including Medline, Pubmed (non‐Medline), CINAHL, PsycINFO, Embase, Emcare and Cochrane central register of controlled trials) will be searched from inception through 2020 to identify relevant randomized controlled trials testing interventions to improve health behaviours and disease‐related knowledge in adults with coronary heart disease. Risk for bias will be assessed using the Cochrane Risk for Bias tool. Data will be synthesized using random‐effects meta‐analyses in Comprehensive Meta‐Analysis Version 3. Heterogeneity will be assessed using Cochrane's Q statistic and the I‐squared statistic will be reported. Meta‐regression will be used to determine the effect of intervention duration. Publication bias will be assessed using funnel plots and Egger's test and which will be adjusted by conducting the trim‐and‐fill test when necessary. Funding for this project began in March 2020. Discussion: We will examine knowledge and behaviour outcomes including physical activity, dietary habits, smoking and medication adherence for patients with coronary heart diseases. This review will be the most comprehensive meta‐analysis of structured patient education interventions to date and the first to analyse the effect of education duration. Impact: The efficacy of patient education on knowledge and behaviour outcomes for patients with coronary heart diseases has not yet been established. This systematic review will determine the efficacy of structured patient education on knowledge and behaviour outcomes and determine whether the duration of patient education influences patient outcomes and thus guide intervention design. PROSPERO registration Number: CRD42020173467. 摘要: 目的: 评估相关疾病知识方面患者结构性教育和冠心病患者健康行为改变的效果 设计: 系统评估和包括教育持续时间方面元回归的元分析 方法: 我们将检索7个数据库(包括联机医学文献分析和检索系统、文献服务检索系统(non ‐ Medline)、护理学数据库、心理学文摘、荷兰医学文摘、紧急医疗护理数据库和科克伦对照试验中央登记册), 以确定相关的随机对照试验, 以测验促进冠心病成人患者健康行为和疾病相关知识的干预措施。使用科克伦偏差风险工具评估偏差风险。数据将在综合元分析第3版中使用随机效应元分析进行合成。采用科克伦Q统计量评估异质性, 并报告I ‐ squared统计量。元回归将用于测定干预时间的影响。偏差发表将通过漏斗图和艾格斯测验进行评估, 并在必要时通过剪补试验进行调整。于2020年3月开始向这项项目提供资金。 讨论: 我们将检验冠心病患者的知识和行为结果, 包括体育活动、饮食习惯、吸烟和药物依从性。本次评估将是迄今为止结构化患者教育干预措施最全面的元分析, 也是首次对教育时长的影响进行分析。 影响: 对冠心病患者进行知识和行为教育的有效性尚未确定。此次评估将测定知识行为效果方面结构化患者教育的有效性, 并测定患者教育的时间是否影响患者结果, 从而指导干预设计。PROSPERO注册号:CRD42020173467。